Studi Penggunaan Safranin dan Kolkisin dalam Pengamatan Kromosom pada Sel Akar Bawang Bombay (Allium cepa Var) - Noval Febriadi; Nofisulastri Nofisulastri; Akhmad Sukri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Based on the results of initial observations it was found that the use of safranin and colchicine showed less than optimal results. The purpose of this study was to observe the phases of mitotic division seen in the use of safranin and colchicine in onion (Allium cepa Var) root cells. The stages of the research included the stages of making preparations, namely root growth, root cutting, fixation, maceration, staining, and squashing. and continued with the observation of the phase of mitotic division which appeared microscopically. The data obtained were from the results of observing the cleavage phase in the chromosomes of the onion root cells, then analyzed descriptively and then comparatively to show what cleavage phases were due to safranin and colchicine staining with different soaking times. Based on the observed cell division phase of onion (Allium cepa Var) roots, safranin was more effective than colchicine with 30 minutes of soaking time.